Question
Let \( f(x)=x^{2}-3 \) and \( g(x)=\sqrt{x+7} \). Find \( f(g(2)) \) O 6 O \( 2 \sqrt{2} \)
Ask by Campbell Love. in the United States
Feb 03,2025
Real Tutor Solution
Tutor-Verified Answer
Answer
\( f(g(2)) = 6 \)
Solution
To find \( f(g(2)) \), we'll follow these steps:
1. **Calculate \( g(2) \):**
\[
g(x) = \sqrt{x + 7}
\]
\[
g(2) = \sqrt{2 + 7} = \sqrt{9} = 3
\]
2. **Now, compute \( f(g(2)) = f(3) \):**
\[
f(x) = x^2 - 3
\]
\[
f(3) = 3^2 - 3 = 9 - 3 = 6
\]
So, \( f(g(2)) = 6 \).
**Answer:** 6
Reviewed and approved by the UpStudy tutoring team
Like
error msg
Explain
Simplify this solution
Beyond the Answer
To find \( f(g(2)) \), we first need to evaluate \( g(2) \). Starting with the function \( g(x) = \sqrt{x + 7} \): \[ g(2) = \sqrt{2 + 7} = \sqrt{9} = 3. \] Now, we substitute this value into the function \( f(x) = x^2 - 3 \): \[ f(g(2)) = f(3) = 3^2 - 3 = 9 - 3 = 6. \] Thus, the result is \( \boxed{6} \).